(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The more independent a person’s thinking is, the more enterprising he will be. The freer a person thinks, the more inquisitive and creative he becomes. When a developing person gets rid of the authority of adults in the family, teachers at school, and acts according to his mental and physical abilities, the child develops a sense of responsibility for his actions. He will have his own opinion. The thinker always bases his views and defends them when necessary. Therefore, in our country, special attention is paid to the education of a harmoniously developed generation of independent thinkers.